The Highs and Lows of Tourism in Pokhara: A Community and Environmental Impact Assessment - Baral, Rekha (Himalayan Biodiversity, 2025)
Tourism development produces both beneficial and adverse effects on host destinations, necessitating comprehensive impact assessments to ensure long-term industry sustainability. While such evaluations are crucial, they remain notably scarce in Nepal's context. This study examines the economic, social, and environmental costs and benefits of tourism in Pokhara - the nation's premier tourism hub renowned as an iconic destination for both domestic and international visitors. Utilizing a mixed-methods approach incorporating questionnaire surveys, focus group discussions, and personal interviews, data were collected on various impact dimensions, which were subsequently analyzed through a Leopold matrix framework. The findings demonstrate that while tourism generates significant socioeconomic benefits for the local community, the cumulative negative impacts threaten to outweigh these advantages. These results underscore the urgent need for innovative policy interventions to effectively mitigate tourism's detrimental effects while preserving its valuable contributions.